Circus aerialism and emotional labour. Issue 2 (1st November 2020) - Walby, Kevin; Spencer, Dale
Abstract : Hochschild (1983) introduced the idea of emotional labour to examine how emotions are performed and managed in work settings. Recent writings have extended Hochschild's works on emotional labour by focusing on the body and collective emotions. Contributing to this literature, we draw on interviews conducted with circus aerialists from several Canadian cities to understand the complexities of emotions, performance and work. Drawing from interviews with 31 aerialists, we examine what aerialists say about emotion management during their performances and travels. We analyse how emotional labour overlaps with the bodily control necessary to engage in circus aerialism as a form of risky work. We also examine how emotional labour is conducted in relation to audience type and the emotional climates that emerge at the group level in aerialist troupes. We conclude by discussing what these findings mean for literatures on emotions and on circus work.